Preparation method of negative oxygen ion water-based paint

By using raw materials such as silicon acrylic emulsion in water-based coatings and adding modified agents and multi-balance reinforcement agents that are mixed with kaolin to adjust the intake of negative oxygen ion release, mechanical impact and flame retardancy in existing water-based coatings, the shortcomings of existing water-based coatings in terms of negative oxygen ion release, mechanical impact and flame retardancy are solved, and higher performance coordination and stability are achieved.

CN119662081AInactive Publication Date: 2025-03-21OXYGEN INJECTION LOVE (HEBEI) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411944477.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing water-based coatings have poor performance in negative oxygen ion release properties, mechanical impact properties and flame retardancy, and have poor acid and alkali resistance and cold and heat stability, which limits the efficiency of the product.

Method used

Silica acrylic emulsion is combined with light calcium powder, functional additives, film forming additives, dispersants and alkaline regulators, and modified kaolin and multi-balance reinforcement agents are added. Through blending and ultrasonic treatment, the performance coordination and stability of the product are optimized.

Benefits of technology

It significantly improves the negative oxygen ion release, mechanical impact performance and flame retardancy of negative oxygen ion water-based coatings, and improves the acid, alkali and hot and cold stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005213311260000131
    Figure BDA0005213311260000131
  • Figure BDA0005213311260000141
    Figure BDA0005213311260000141
  • Figure BDA0005213311260000142
    Figure BDA0005213311260000142
Patent Text Reader

Abstract

The invention relates to the technical field of water-based paint, in particular to a preparation method of negative oxygen ion water-based paint. Comprising the following steps: weighing the following raw materials in parts by weight: 25-30 parts of silicone acrylic emulsion, 8-12 parts of light calcium carbonate powder, 7-11 parts of a modifying agent mixed with kaolin, 7-9 parts of a functional additive, 5-8 parts of a Duozheng reinforcing agent, 3-5 parts of a coalescing agent, 1-2 parts of a dispersing agent, 0.04-0.06 part of an alkaline regulator and 37-39 parts of deionized water. According to the negative oxygen ion water-based paint, the silicone acrylic emulsion is matched with the light calcium carbonate powder, the functional additive, the coalescing agent, the dispersing agent and the alkaline regulator, the functional additive comprises tourmaline powder, a flame retardant and an antibacterial agent, and the flame-retardant, antibacterial and negative oxygen ion release functions of a product are optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water-based coatings, and in particular to a method for preparing a negative oxygen ion water-based coating. Background Art

[0002] Water-based paint is a paint that uses water as a solvent or dispersion medium. It is a relatively new type of paint on the paint market, including three types: water-soluble paint, water-dilutable paint, and water-dispersible paint (latex paint). Water-based paint uses water-soluble resin as a film-forming material, represented by polyvinyl alcohol and its various modified products. In addition, there are water-soluble alkyd resins, water-soluble epoxy resins, and inorganic polymer water-based resins. For water-based paint, water-based high-grade coatings are manufactured, which can be used to paint the interior of new and old cars and the interior walls of new and old houses.

[0003] Existing water-based coatings have poor negative oxygen ion release performance, and the products also have poor mechanical impact properties and flame retardancy. It is difficult for the products to achieve coordinated improvements in negative oxygen ion release, mechanical impact properties and flame retardancy. At the same time, the products have poor acid and alkali resistance and poor heat and cold stability, which limits the product's use efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing a negative oxygen ion water-based coating to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a method for preparing a negative oxygen ion water-based paint, comprising the following steps:

[0007] Step 1: weigh the raw materials according to weight:

[0008] 25-30 parts of silicone-acrylic emulsion, 8-12 parts of light calcium powder, 7-11 parts of performance-improving agent mixed with kaolin, 7-9 parts of functional additives, 5-8 parts of multi-balance reinforcing agent, 3-5 parts of film-forming aid, 1-2 parts of dispersant, 0.04-0.06 parts of alkaline regulator, and 37-39 parts of deionized water;

[0009] Step 2, light calcium powder, the performance-improving agent mixed with kaolin, the functional additive and the multi-balance reinforcing agent are uniformly blended to obtain a first product;

[0010] Step 3, then uniformly blending the film-forming aid, dispersant, and alkaline regulator to obtain a second product;

[0011] Step 4: The first product and the second product are further mixed with the silicone acrylic emulsion and deionized water to obtain a negative oxygen ion water-based coating.

[0012] Preferably, the solid content of the silicone acrylic emulsion is 40-45%;

[0013] The film-forming aid is propylene glycol butyl ether; the dispersant is dispersant 5040; the alkaline regulator is sodium hydroxide; the functional additives include 6 to 8 parts by weight of tourmaline powder, 4 to 7 parts of flame retardant, and 2 to 4 parts of antibacterial agent; the flame retardant is magnesium hydroxide; and the antibacterial agent is nano silver powder.

[0014] Preferably, the preparation method of the performance-improving agent blended with kaolin is:

[0015] S01: Place the flaky aluminum oxide in a sufficient amount of 5% by mass potassium permanganate solution and stir thoroughly, then wash, filter and dry;

[0016] S02: irradiating the dried flaky aluminum oxide in a proton irradiation box for 10 to 15 minutes at an irradiation power of 350 to 400 W, and obtaining a flaky aluminum oxide irradiation agent after the irradiation is completed;

[0017] S03: 3-5 parts of sodium silicate solution, 2-3 parts of glass fiber and 5-8 parts of barium nitrate solution are mixed evenly, and then 2-4 parts of sodium lignin sulfonate and 1-3 parts of silane coupling agent KH550 are added and mixed thoroughly to obtain a modified solution;

[0018] 5 to 8 parts of flaky aluminum oxide irradiating agent and 4 to 7 parts of improvement liquid are mixed and ultrasonically treated, and the ultrasonic treatment is terminated to obtain the flaky aluminum oxide improvement liquid;

[0019] S04: The flaky alumina modifying liquid and the kaolin-adjusting agent are mixed in a weight ratio of 3:(5-6), and the mixture is ball-milled at a speed of 1200-1500 r / min for 1 hour. After the ball milling is completed, the mixture is filtered and dried to obtain the modifying agent with kaolin-adjusting agent.

[0020] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the barium nitrate solution is 3-6%.

[0021] Preferably, the ultrasonic power of the blending ultrasonic treatment is 350-400 W, and the ultrasonic time is 10-20 min.

[0022] Preferably, the preparation method of the kaolin blending agent is:

[0023] The kaolin is first heat treated at 150-160°C for 15-20 minutes, then cooled to 60°C at a rate of 2-4°C / min, and kept warm;

[0024] The heat-insulated kaolin is immersed in a sufficient amount of a transfer liquid for stirring and modification treatment. After the stirring is completed, the mixture is filtered and dried to obtain a kaolin-admixed transfer agent. The transfer liquid comprises the following raw materials in parts by weight: 3 to 5 parts of hydroxyapatite, 1 to 2 parts of stearic acid, 2 to 4 parts of nano calcium carbonate and 4 to 7 parts of lanthanum nitrate solution.

[0025] Preferably, the mass fraction of the lanthanum nitrate solution is 2-5%; the stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring is 35-40 min.

[0026] Preferably, the preparation method of the multi-balance reinforcing agent is:

[0027] S11: stirring the aluminum borate whiskers in a sufficient amount of acid solution, then washing with water and drying to obtain acid-treated aluminum borate whiskers;

[0028] S12: 3-5 parts of nano-silicon dioxide, 1-3 parts of silicon carbide, 4-7 parts of yttrium nitrate solution and 1-2 parts of 5% by mass sodium dodecylbenzene sulfonate solution are mixed to obtain a nano-silicon dioxide liquid;

[0029] S13: stirring the acid-treated aluminum borate whiskers and nano-silicon dioxide liquid in a weight ratio of 2:5, washing with water, filtering, and drying to obtain a multi-balance reinforcing agent.

[0030] Preferably, the acid solution is a sulfuric acid solution with a mass fraction of 5 to 7%; the mass fraction of the yttrium nitrate solution is 2 to 4%.

[0031] Preferably, the stirring speed of the stirring treatment is 500-600 r / min, and the stirring time is 1-2 h.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The negative oxygen ion water-based paint of the present invention adopts silicone acrylic emulsion, light calcium powder, functional additives, film-forming aids, dispersants and alkaline regulator raw materials. The functional additives include tourmaline powder, flame retardant, antibacterial agent, and optimize the flame retardant, antibacterial and negative oxygen ion release functions of the product. At the same time, the performance-improving agent and multi-balance reinforcing agent added by kaolin are coordinated and coordinated to enhance the synergy. The negative oxygen ion release, mechanical impact performance and flame retardancy of the product are coordinated and improved. At the same time, the acid and alkali resistance and cold and heat stability of the product are remarkable. The performance-improving agent added by kaolin is a flake The flaky alumina is treated with potassium permanganate solution and then irradiated with protons to stimulate the active performance of the flaky alumina. At the same time, sodium silicate solution, glass fiber, barium nitrate solution, sodium lignin sulfonate and silane coupling agent KH550 are used to mix to obtain a modified liquid. The raw materials in the modified liquid cooperate with each other and work together. The glass fiber is used as a needle-like structure for reinforcement. At the same time, the flaky alumina is carried by the flaky structure. In combination with a specific modified liquid, the performance coordination and performance stability of the product are optimized. At the same time, kaolin is added to adjust the agent. The kaolin in the kaolin blending agent is first heat-treated at 150-160°C for 15-20 minutes, and then cooled to 60°C at a rate of 2-4°C / min, and kept warm to optimize the interlamellar spacing and activity of the kaolin. At the same time, it is stirred and modified in the blending liquid. The hydroxyapatite, stearic acid, nano-calcium carbonate and lanthanum nitrate solution in the blending liquid are coordinated together. The hydroxyapatite is combined with nano-calcium carbonate to strengthen the interlamellar spacing, and then the flaky alumina modification liquid is coordinated to improve the performance of the product. The invention is further improved; the multi-balance reinforcing agent adopts aluminum borate whiskers treated with acid solution to optimize its activity, and then stirs with nano-silicon dioxide liquid, and the nano-silicon dioxide, silicon carbide, yttrium nitrate solution and 5% by mass sodium dodecylbenzene sulfonate solution in the nano-silicon dioxide liquid are fully blended, and the aluminum borate whiskers are improved by co-matching with nano-silicon dioxide and silicon carbide to further strengthen the system structure, and the multi-balance reinforcing agent is better coordinated and optimized to mix the performance-improving agent added with kaolin, so that the performance of the product is further improved. DETAILED DESCRIPTION

[0034] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] A method for preparing a negative oxygen ion water-based coating of the present embodiment comprises the following steps:

[0036] Step 1: weigh the raw materials according to weight:

[0037] 25-30 parts of silicone-acrylic emulsion, 8-12 parts of light calcium powder, 7-11 parts of performance-improving agent mixed with kaolin, 7-9 parts of functional additives, 5-8 parts of multi-balance reinforcing agent, 3-5 parts of film-forming aid, 1-2 parts of dispersant, 0.04-0.06 parts of alkaline regulator, and 37-39 parts of deionized water;

[0038] Step 2, light calcium powder, the performance-improving agent mixed with kaolin, the functional additive and the multi-balance reinforcing agent are uniformly blended to obtain a first product;

[0039] Step 3, then uniformly blending the film-forming aid, dispersant, and alkaline regulator to obtain a second product;

[0040] Step 4: The first product and the second product are further mixed with the silicone acrylic emulsion and deionized water to obtain a negative oxygen ion water-based coating.

[0041] The solid content of the silicone-acrylic emulsion in this embodiment is 40-45%;

[0042] The film-forming aid is propylene glycol butyl ether; the dispersant is dispersant 5040; the alkaline regulator is sodium hydroxide; the functional additives include 6 to 8 parts by weight of tourmaline powder, 4 to 7 parts of flame retardant, and 2 to 4 parts of antibacterial agent; the flame retardant is magnesium hydroxide; and the antibacterial agent is nano silver powder.

[0043] The preparation method of the performance-improving agent mixed with kaolin in this embodiment is as follows:

[0044] S01: Place the flaky aluminum oxide in a sufficient amount of 5% by mass potassium permanganate solution and stir thoroughly, then wash, filter and dry;

[0045] S02: irradiating the dried flaky aluminum oxide in a proton irradiation box for 10 to 15 minutes at an irradiation power of 350 to 400 W, and obtaining a flaky aluminum oxide irradiation agent after the irradiation is completed;

[0046] S03: 3-5 parts of sodium silicate solution, 2-3 parts of glass fiber and 5-8 parts of barium nitrate solution are mixed evenly, and then 2-4 parts of sodium lignin sulfonate and 1-3 parts of silane coupling agent KH550 are added and mixed thoroughly to obtain a modified solution;

[0047] 5 to 8 parts of flaky aluminum oxide irradiating agent and 4 to 7 parts of improvement liquid are mixed and ultrasonically treated, and the ultrasonic treatment is terminated to obtain the flaky aluminum oxide improvement liquid;

[0048] S04: The flaky alumina modifying liquid and the kaolin-adjusting agent are mixed in a weight ratio of 3:(5-6), and the mixture is ball-milled at a speed of 1200-1500 r / min for 1 hour. After the ball milling is completed, the mixture is filtered and dried to obtain the modifying agent with kaolin-adjusting agent.

[0049] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the mass fraction of the barium nitrate solution is 3-6%.

[0050] The ultrasonic power of the blending ultrasonic treatment in this embodiment is 350-400 W, and the ultrasonic time is 10-20 min.

[0051] The preparation method of the kaolin blending agent of this embodiment is as follows:

[0052] The kaolin is first heat treated at 150-160°C for 15-20 minutes, then cooled to 60°C at a rate of 2-4°C / min, and kept warm;

[0053] The heat-insulated kaolin is immersed in a sufficient amount of a transfer liquid for stirring and modification treatment. After the stirring is completed, the mixture is filtered and dried to obtain a kaolin-admixed transfer agent. The transfer liquid comprises the following raw materials in parts by weight: 3 to 5 parts of hydroxyapatite, 1 to 2 parts of stearic acid, 2 to 4 parts of nano calcium carbonate and 4 to 7 parts of lanthanum nitrate solution.

[0054] The mass fraction of the lanthanum nitrate solution of this embodiment is 2-5%; the stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring is 35-40 min.

[0055] The preparation method of the multi-balance reinforcing agent of this embodiment is:

[0056] S11: stirring the aluminum borate whiskers in a sufficient amount of acid solution, then washing with water and drying to obtain acid-treated aluminum borate whiskers;

[0057] S12: 3-5 parts of nano-silicon dioxide, 1-3 parts of silicon carbide, 4-7 parts of yttrium nitrate solution and 1-2 parts of 5% by mass sodium dodecylbenzene sulfonate solution are mixed to obtain a nano-silicon dioxide liquid;

[0058] The acid-treated aluminum borate whiskers and nano-silicon dioxide liquid are stirred in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a multi-balance reinforcing agent.

[0059] The acid solution in this embodiment is a sulfuric acid solution with a mass fraction of 5-7%; the mass fraction of the yttrium nitrate solution is 2-4%.

[0060] The stirring speed of the stirring treatment in this embodiment is 500-600 r / min, and the stirring is performed for 1-2 hours.

[0061] Example 1.

[0062] A method for preparing a negative oxygen ion water-based coating of the present embodiment comprises the following steps:

[0063] Step 1: weigh the raw materials according to weight:

[0064] 25 parts of silicone-acrylic emulsion, 8 parts of light calcium powder, 7 parts of performance-improving agent mixed with kaolin, 7 parts of functional additives, 5 parts of multi-balancing reinforcing agent, 3 parts of film-forming aid, 1 part of dispersant, 0.04 parts of alkaline regulator, and 37 parts of deionized water;

[0065] Step 2, light calcium powder, the performance-improving agent mixed with kaolin, the functional additive and the multi-balance reinforcing agent are uniformly blended to obtain a first product;

[0066] Step 3, then uniformly blending the film-forming aid, dispersant, and alkaline regulator to obtain a second product;

[0067] Step 4: The first product and the second product are further mixed with the silicone acrylic emulsion and deionized water to obtain a negative oxygen ion water-based coating.

[0068] The solid content of the silicone-acrylic emulsion in this embodiment is 40%;

[0069] The film-forming aid is propylene glycol butyl ether; the dispersant is dispersant 5040; the alkaline regulator is sodium hydroxide; the functional additives include 6 parts by weight of tourmaline powder, 4 parts of flame retardant, and 2 parts of antibacterial agent; the flame retardant is magnesium hydroxide; and the antibacterial agent is nano silver powder.

[0070] The preparation method of the performance-improving agent mixed with kaolin in this embodiment is as follows:

[0071] S01: Place the flaky aluminum oxide in a sufficient amount of 5% by mass potassium permanganate solution and stir thoroughly, then wash, filter and dry;

[0072] S02: irradiating the dried flaky aluminum oxide in a proton irradiation box for 10 minutes at an irradiation power of 350 W, and obtaining a flaky aluminum oxide irradiation agent after the irradiation is completed;

[0073] S03: 3 parts of sodium silicate solution, 2 parts of glass fiber and 5 parts of barium nitrate solution are mixed evenly, and then 2 parts of sodium lignin sulfonate and 1 part of silane coupling agent KH550 are added and mixed thoroughly to obtain an improved performance solution;

[0074] 5 parts of flaky aluminum oxide irradiating agent and 4 parts of modified liquid are mixed and ultrasonically treated, and the ultrasonic treatment is terminated to obtain the flaky aluminum oxide modified liquid;

[0075] S04: The flaky alumina modifying liquid and the kaolin-adjusting agent are mixed in a weight ratio of 3:5 and subjected to ball milling at a ball milling speed of 1200 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the modifying agent blended with kaolin.

[0076] The mass fraction of the sodium silicate solution in this embodiment is 2%; the mass fraction of the barium nitrate solution is 3%.

[0077] The ultrasonic power of the blending ultrasonic treatment in this embodiment is 350W, and the ultrasonic time is 10min.

[0078] The preparation method of the kaolin blending agent of this embodiment is as follows:

[0079] The kaolin was first heat treated at 150°C for 15 min, then cooled to 60°C at a rate of 2°C / min and kept warm;

[0080] The insulated kaolin is immersed in a sufficient amount of the adjusting liquid and stirred for modification. After the stirring is completed, it is filtered and dried to obtain a kaolin adjusting agent. The adjusting liquid includes the following raw materials in parts by weight: 3 parts of hydroxyapatite, 1 part of stearic acid, 2 parts of nano calcium carbonate and 4 parts of lanthanum nitrate solution.

[0081] The mass fraction of the lanthanum nitrate solution in this embodiment is 2%; the stirring speed of the stirring modification treatment is 550r / min, and the stirring is 35min.

[0082] The preparation method of the multi-balance reinforcing agent of this embodiment is:

[0083] S11: stirring the aluminum borate whiskers in a sufficient amount of acid solution, then washing with water and drying to obtain acid-treated aluminum borate whiskers;

[0084] S12: 3 parts of nano-silicon dioxide, 1 part of silicon carbide, 4 parts of yttrium nitrate solution and 1 part of 5% by mass sodium dodecylbenzene sulfonate solution are mixed to obtain a nano-silicon dioxide liquid;

[0085] The acid-treated aluminum borate whiskers and nano-silicon dioxide liquid are stirred in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a multi-balance reinforcing agent.

[0086] The acid solution in this embodiment is a sulfuric acid solution with a mass fraction of 5%; the mass fraction of the yttrium nitrate solution is 2%.

[0087] The stirring speed of the stirring process in this embodiment is 500 r / min, and the stirring is performed for 1 hour.

[0088] Example 2.

[0089] A method for preparing a negative oxygen ion water-based coating of the present embodiment comprises the following steps:

[0090] Step 1: weigh the raw materials according to weight:

[0091] 30 parts of silicone-acrylic emulsion, 12 parts of light calcium powder, 11 parts of performance-improving agent mixed with kaolin, 9 parts of functional additives, 8 parts of multi-balance reinforcing agent, 5 parts of film-forming aid, 2 parts of dispersant, 0.06 parts of alkaline regulator, and 39 parts of deionized water;

[0092] Step 2, light calcium powder, the performance-improving agent mixed with kaolin, the functional additive and the multi-balance reinforcing agent are uniformly blended to obtain a first product;

[0093] Step 3, then uniformly blending the film-forming aid, dispersant, and alkaline regulator to obtain a second product;

[0094] Step 4: The first product and the second product are further mixed with the silicone acrylic emulsion and deionized water to obtain a negative oxygen ion water-based coating.

[0095] The solid content of the silicone-acrylic emulsion in this embodiment is 45%;

[0096] The film-forming aid is propylene glycol butyl ether; the dispersant is dispersant 5040; the alkaline regulator is sodium hydroxide; the functional additives include 8 parts by weight of tourmaline powder, 7 parts of flame retardant, and 4 parts of antibacterial agent; the flame retardant is magnesium hydroxide; and the antibacterial agent is nano silver powder.

[0097] The preparation method of the performance-improving agent mixed with kaolin in this embodiment is as follows:

[0098] S01: Place the flaky aluminum oxide in a sufficient amount of 5% by mass potassium permanganate solution and stir thoroughly, then wash, filter and dry;

[0099] S02: irradiating the dried flaky aluminum oxide in a proton irradiation box for 15 minutes at an irradiation power of 400 W, and obtaining a flaky aluminum oxide irradiation agent after the irradiation is completed;

[0100] S03: 5 parts of sodium silicate solution, 3 parts of glass fiber and 8 parts of barium nitrate solution are mixed evenly, and then 4 parts of sodium lignin sulfonate and 3 parts of silane coupling agent KH550 are added and mixed thoroughly to obtain an improved performance solution;

[0101] 8 parts of flaky aluminum oxide irradiating agent and 7 parts of improvement liquid are mixed and ultrasonically treated, and the ultrasonic treatment is terminated to obtain the flaky aluminum oxide improvement liquid;

[0102] S04: The flaky alumina modifying liquid and the kaolin-adjusting agent are mixed in a weight ratio of 3:6 and subjected to ball milling at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, the mixture is filtered and dried to obtain the modifying agent blended with kaolin.

[0103] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the barium nitrate solution is 6%.

[0104] The ultrasonic power of the blending ultrasonic treatment in this embodiment is 400 W, and the ultrasonic time is 20 min.

[0105] The preparation method of the kaolin blending agent of this embodiment is as follows:

[0106] The kaolin was first heat treated at 160°C for 20 min, then cooled to 60°C at a rate of 4°C / min and kept warm;

[0107] The heat-insulated kaolin is immersed in a sufficient amount of the adjusting liquid and stirred for modification. After the stirring is completed, it is filtered and dried to obtain a kaolin-admixed adjusting agent; the adjusting liquid includes the following raw materials in parts by weight: 5 parts of hydroxyapatite, 2 parts of stearic acid, 4 parts of nano calcium carbonate and 7 parts of lanthanum nitrate solution.

[0108] The mass fraction of the lanthanum nitrate solution in this embodiment is 5%; the stirring speed of the stirring modification treatment is 750r / min, and the stirring is 40min.

[0109] The preparation method of the multi-balance reinforcing agent of this embodiment is:

[0110] S11: stirring the aluminum borate whiskers in a sufficient amount of acid solution, then washing with water and drying to obtain acid-treated aluminum borate whiskers;

[0111] S12: 5 parts of nano-silicon dioxide, 3 parts of silicon carbide, 7 parts of yttrium nitrate solution and 2 parts of 5% by mass sodium dodecylbenzene sulfonate solution are mixed to obtain a nano-silicon dioxide liquid;

[0112] The acid-treated aluminum borate whiskers and nano-silicon dioxide liquid are stirred in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a multi-balance reinforcing agent.

[0113] The acid solution in this embodiment is a sulfuric acid solution with a mass fraction of 7%; the mass fraction of the yttrium nitrate solution is 4%.

[0114] The stirring speed of the stirring process in this embodiment is 600 r / min, and the stirring is performed for 2 hours.

[0115] Example 3.

[0116] A method for preparing a negative oxygen ion water-based coating of the present embodiment comprises the following steps:

[0117] Step 1: weigh the raw materials according to weight:

[0118] 27.5 parts of silicone-acrylic emulsion, 10 parts of light calcium powder, 9 parts of performance-improving agent mixed with kaolin, 8 parts of functional additives, 6.5 parts of multi-balancing reinforcing agent, 4 parts of film-forming aid, 1.5 parts of dispersant, 0.05 parts of alkaline regulator, and 38 parts of deionized water;

[0119] Step 2, light calcium powder, the performance-improving agent mixed with kaolin, the functional additive and the multi-balance reinforcing agent are uniformly blended to obtain a first product;

[0120] Step 3, then uniformly blending the film-forming aid, dispersant, and alkaline regulator to obtain a second product;

[0121] Step 4: The first product and the second product are further mixed with the silicone acrylic emulsion and deionized water to obtain a negative oxygen ion water-based coating.

[0122] The solid content of the silicone-acrylic emulsion in this embodiment is 42.5%;

[0123] The film-forming aid is propylene glycol butyl ether; the dispersant is dispersant 5040; the alkaline regulator is sodium hydroxide; the functional additives include 7 parts by weight of tourmaline powder, 5.5 parts of flame retardant, and 3 parts of antibacterial agent; the flame retardant is magnesium hydroxide; and the antibacterial agent is nano silver powder.

[0124] The preparation method of the performance-improving agent mixed with kaolin in this embodiment is as follows:

[0125] S01: Place the flaky aluminum oxide in a sufficient amount of 5% by mass potassium permanganate solution and stir thoroughly, then wash, filter and dry;

[0126] S02: irradiating the dried flaky aluminum oxide in a proton irradiation box for 12.5 minutes at an irradiation power of 375 W, and obtaining a flaky aluminum oxide irradiation agent after the irradiation is completed;

[0127] S03: 4 parts of sodium silicate solution, 2.5 parts of glass fiber and 6.5 parts of barium nitrate solution are mixed evenly, and then 3 parts of sodium lignin sulfonate and 2 parts of silane coupling agent KH550 are added and mixed thoroughly to obtain an improved performance solution;

[0128] 6.5 parts of flaky aluminum oxide irradiating agent and 5.5 parts of improving liquid are mixed and ultrasonically treated, and the ultrasonic treatment is terminated to obtain flaky aluminum oxide improving liquid;

[0129] S04: The flaky alumina modifying liquid and the kaolin-adjusting agent are mixed in a weight ratio of 3:5.5, and the mixture is ball-milled at a speed of 350 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the modifying agent mixed with kaolin.

[0130] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the mass fraction of the barium nitrate solution is 4.5%.

[0131] The ultrasonic power of the blending ultrasonic treatment in this embodiment is 375W, and the ultrasonic time is 15min.

[0132] The preparation method of the kaolin blending agent of this embodiment is as follows:

[0133] The kaolin was first heat treated at 155°C for 17.5 min, then cooled to 60°C at a rate of 3°C / min and kept warm;

[0134] The insulated kaolin is immersed in a sufficient amount of the adjusting liquid and stirred for modification. After the stirring is completed, it is filtered and dried to obtain a kaolin adjusting agent. The adjusting liquid includes the following raw materials in parts by weight: 4 parts of hydroxyapatite, 1.5 parts of stearic acid, 3 parts of nano calcium carbonate and 5.5 parts of lanthanum nitrate solution.

[0135] The mass fraction of the lanthanum nitrate solution in this embodiment is 3.5%; the stirring speed of the stirring modification treatment is 600r / min, and the stirring time is 37.5min.

[0136] The preparation method of the multi-balance reinforcing agent of this embodiment is:

[0137] S11: stirring the aluminum borate whiskers in a sufficient amount of acid solution, then washing with water and drying to obtain acid-treated aluminum borate whiskers;

[0138] S12: 4 parts of nano-silicon dioxide, 2 parts of silicon carbide, 5.5 parts of yttrium nitrate solution and 1.5 parts of 5% by mass sodium dodecylbenzene sulfonate solution are mixed to obtain a nano-silicon dioxide liquid;

[0139] The acid-treated aluminum borate whiskers and nano-silicon dioxide liquid are stirred in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water, filtered and dried to obtain a multi-balance reinforcing agent.

[0140] The acid solution in this embodiment is a sulfuric acid solution with a mass fraction of 6%; the mass fraction of the yttrium nitrate solution is 3%.

[0141] The stirring speed of the stirring process in this embodiment is 550 r / min, and the stirring is performed for 1.5 hours.

[0142] Comparative Example 1.

[0143] The difference from Example 3 is that no performance-improving agent blended with kaolin is added.

[0144] Comparative Example 2.

[0145] The difference from Example 3 is that no flaky alumina performance-improving liquid is added in the preparation of the performance-improving agent blended with kaolin.

[0146] Comparative Example 3.

[0147] The difference from Example 3 is that no flaky alumina irradiating agent is added in the preparation of the flaky alumina modifying solution.

[0148] Comparative Example 4.

[0149] The difference from Example 3 is that no modifying liquid is added in the preparation of the flaky alumina modifying liquid.

[0150] Comparative Example 5.

[0151] The difference from Example 3 is that no sodium silicate solution and sodium lignin sulfonate are added to the improvement solution.

[0152] Comparative Example 6.

[0153] The difference from Example 3 is that glass fiber and silane coupling agent KH550 are not added to the improvement liquid.

[0154] Comparative Example 7.

[0155] The difference from Example 3 is that no barium nitrate solution is added to the modified solution.

[0156] Comparative Example 8.

[0157] The difference from Example 3 is that no kaolin blending agent is added in the preparation of the performance-improving agent blended with kaolin.

[0158] Comparative Example 9.

[0159] The difference from Example 3 is that no multi-functional reinforcing agent is added.

[0160] Comparative Example 10.

[0161] The difference from Example 3 is that no acid-treated aluminum borate whiskers were added in the preparation of the multi-balance reinforcing agent.

[0162] Comparative Example 11.

[0163] The difference from Example 3 is that no nano-silica liquid is added in the preparation of the multi-balance reinforcing agent.

[0164] Comparative Example 12.

[0165] The difference from Example 3 is that no nano silicon dioxide or silicon carbide is added to the nano silicon dioxide liquid.

[0166] The products of Examples 1 to 3 and Comparative Examples 1 to 12 were subjected to conventional performance tests on negative oxygen ion release, mechanical impact properties and flame retardancy. The test results are as follows

[0167]

[0168]

[0169] Place the product in 2% hydrochloric acid mist for 12 hours, then in 5% sodium hydroxide mist for 12 hours, at 65°C for 12 hours, and then at -5°C for 12 hours. The above is one cycle. Repeat the test 10 times to test the acid and alkali resistance, cold and heat stability of the product.

[0170]

[0171]

[0172] It can be seen from comparative examples 1-12 and embodiments 1-3 as well as acid and alkali resistance and cold and heat stability tests;

[0173] The product of Example 3 has excellent negative oxygen ion release, mechanical impact resistance and flame retardancy, and the three properties can be improved in a coordinated manner. In addition, the product has excellent performance stability under acid and alkali resistance and cold and hot conditions;

[0174] The present invention does not add a performance-improving agent mixed with kaolin and does not add one of the multi-balance reinforcing agents. The performance of the product is obviously deteriorated, and the acid and alkali resistance and cold and hot stability of the product are obviously reduced. The two are used in coordination to synergistically enhance the performance of the product, and the performance of the product is obviously improved;

[0175] The performance of the products showed a significant deterioration trend when the kaolin-blended performance modifier was not added without the addition of flaky alumina performance modifier and the kaolin-blended performance modifier was not added in the preparation of the kaolin-blended performance modifier, especially when the kaolin-blended performance modifier was not added;

[0176] The performance of the products showed a trend of deterioration to varying degrees when no flaky alumina irradiating agent was added in the preparation of the flaky alumina improving liquid, no improving liquid was added in the preparation of the flaky alumina improving liquid, no sodium silicate solution and sodium lignin sulfonate were added to the improving liquid, no glass fiber and silane coupling agent KH550 were added to the improving liquid, and no barium nitrate solution was added to the improving liquid. The performance of the flaky alumina improving liquid prepared by combining the improving liquid obtained by the method of the present invention with the flaky alumina irradiating agent was the most significant. The effects of other methods were not as obvious as those of the present invention.

[0177] The performance of the products without adding acid-treated aluminum borate whiskers, nano-silicon dioxide liquid, or nano-silicon dioxide and silicon carbide to the nano-silicon dioxide liquid in the preparation of the multi-balance reinforcing agent all tended to deteriorate to varying degrees. The multi-balance reinforcing agent obtained by the specific method of the present invention had the most obvious product performance effect.

[0178] The present invention further explores the product performance by preparing a kaolin-adjusting agent.

[0179] Experimental example 1.

[0180] The only difference from Example 3 is that no adjusting liquid treatment is used in the preparation of the adjusting agent for blending kaolin.

[0181] Experimental example 2.

[0182] The only difference from Example 3 is that no heat-insulating kaolin is added in the preparation of the kaolin blending agent.

[0183] Experimental Example 3.

[0184] The only difference from Example 3 is that no hydroxyapatite is added to the mixing solution.

[0185] Experimental Example 4.

[0186] The only difference from Example 3 is that no nano calcium carbonate is added to the liquid.

[0187] Experimental Example 5.

[0188] The only difference from Example 3 is that stearic acid is not added to the adjusted solution and the lanthanum nitrate solution is replaced by water.

[0189] The performance of the product is tested by its resistance to acid, alkali, cold and heat;

[0190]

[0191] From Experimental Examples 1-5, it can be seen that the performance of the product changes when no heat-insulating kaolin is added in the preparation of the kaolin-adjusting agent. Among the preparation components of the kaolin-adjusting agent, the performance deterioration is the most obvious, followed by the failure to use the adjusting liquid treatment;

[0192] At the same time, no hydroxyapatite was added to the adjusting liquid, no nano-calcium carbonate was added to the adjusting liquid, no stearic acid was added to the adjusting liquid, and water was used instead of the lanthanum nitrate solution. The performance of the product tended to deteriorate to varying degrees. Therefore, the composition of the adjusting liquid is proprietary. The adjusting liquid obtained by the specific method of the present invention is combined with the thermal insulation kaolin of the present invention. The performance effect of the product is most significant. The preparation using other methods instead of adding kaolin adjusting agent is not as significant as the effect of the present invention.

[0193] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0194] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a negative oxygen ion water-based paint, characterized in that: The following steps are involved: Step 1: weigh the raw materials according to weight: 25-30 parts of silicone-acrylic emulsion, 8-12 parts of light calcium powder, 7-11 parts of performance-improving agent mixed with kaolin, 7-9 parts of functional additives, 5-8 parts of multi-balance reinforcing agent, 3-5 parts of film-forming aid, 1-2 parts of dispersant, 0.04-0.06 parts of alkaline regulator, and 37-39 parts of deionized water; Step 2, light calcium powder, the performance-improving agent mixed with kaolin, the functional additive and the multi-balance reinforcing agent are uniformly blended to obtain a first product; Step 3, then uniformly blending the film-forming aid, dispersant, and alkaline regulator to obtain a second product; Step 4: The first product and the second product are further mixed with the silicone acrylic emulsion and deionized water to obtain a negative oxygen ion water-based coating.

2. The method for preparing a negative oxygen ion water-based paint according to claim 1, characterized in that: The solid content of the silicone-acrylic emulsion is 40-45%; The film-forming aid is propylene glycol butyl ether; the dispersant is dispersant 5040; the alkaline regulator is sodium hydroxide; the functional additives include 6 to 8 parts by weight of tourmaline powder, 4 to 7 parts of flame retardant, and 2 to 4 parts of antibacterial agent; the flame retardant is magnesium hydroxide; and the antibacterial agent is nano silver powder.

3. The method for preparing a negative oxygen ion water-based paint according to claim 1, characterized in that: The preparation method of the performance-improving agent mixed with kaolin is as follows: S01: Place the flaky aluminum oxide in a sufficient amount of 5% by mass potassium permanganate solution and stir thoroughly, then wash, filter and dry; S02: irradiating the dried flaky aluminum oxide in a proton irradiation box for 10 to 15 minutes at an irradiation power of 350 to 400 W, and obtaining a flaky aluminum oxide irradiation agent after the irradiation is completed; S03: 3-5 parts of sodium silicate solution, 2-3 parts of glass fiber and 5-8 parts of barium nitrate solution are mixed evenly, and then 2-4 parts of sodium lignin sulfonate and 1-3 parts of silane coupling agent KH550 are added and mixed thoroughly to obtain a modified solution; 5 to 8 parts of flaky aluminum oxide irradiating agent and 4 to 7 parts of improvement liquid are mixed and ultrasonically treated, and the ultrasonic treatment is terminated to obtain the flaky aluminum oxide improvement liquid; S04: The flaky alumina modifying liquid and the kaolin-adjusting agent are mixed in a weight ratio of 3:(5-6), and the mixture is ball-milled at a speed of 1200-1500 r / min for 1 hour. After the ball milling is completed, the mixture is filtered and dried to obtain the modifying agent with kaolin-adjusting agent.

4. The method for preparing a negative oxygen ion water-based paint according to claim 3, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the barium nitrate solution is 3-6%.

5. The method for preparing a negative oxygen ion water-based paint according to claim 3, characterized in that: The ultrasonic power of the blending ultrasonic treatment is 350-400W, and the ultrasonic time is 10-20min.

6. The method for preparing a negative oxygen ion water-based paint according to claim 3, characterized in that: The preparation method of the kaolin blending agent is as follows: The kaolin is first heat treated at 150-160°C for 15-20 minutes, then cooled to 60°C at a rate of 2-4°C / min, and kept warm; The heat-insulated kaolin is immersed in a sufficient amount of a transfer liquid for stirring and modification treatment. After the stirring is completed, the mixture is filtered and dried to obtain a kaolin-admixed transfer agent. The transfer liquid comprises the following raw materials in parts by weight: 3 to 5 parts of hydroxyapatite, 1 to 2 parts of stearic acid, 2 to 4 parts of nano calcium carbonate and 4 to 7 parts of lanthanum nitrate solution.

7. The method for preparing a negative oxygen ion water-based paint according to claim 6, characterized in that: The mass fraction of the lanthanum nitrate solution is 2-5%; the stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring is performed for 35-40 minutes.

8. The method for preparing a negative oxygen ion water-based paint according to claim 6, characterized in that: The preparation method of the multi-balance reinforcing agent is: S11: stirring the aluminum borate whiskers in a sufficient amount of acid solution, then washing with water and drying to obtain acid-treated aluminum borate whiskers; S12: 3-5 parts of nano-silicon dioxide, 1-3 parts of silicon carbide, 4-7 parts of yttrium nitrate solution and 1-2 parts of 5% by mass sodium dodecylbenzene sulfonate solution are mixed to obtain a nano-silicon dioxide liquid; S13: stirring the acid-treated aluminum borate whiskers and nano-silicon dioxide liquid in a weight ratio of 2:5, washing with water, filtering, and drying to obtain a multi-balance reinforcing agent.

9. The method for preparing a negative oxygen ion water-based paint according to claim 8, characterized in that: The acid solution is a sulfuric acid solution with a mass fraction of 5-7%; the mass fraction of the yttrium nitrate solution is 2-4%.

10. The method for preparing a negative oxygen ion water-based paint according to claim 8, characterized in that: The stirring speed of the stirring treatment is 500-600 r / min, and the stirring is performed for 1-2 hours.